Evolving correction factors for economic traits using time series analysisin Murrah buffaloes - GANDHI, R S; SINGH, SURENDRA; SACHDEVA, G K (The Indian Journal of Animal Sciences, 2011)
Lactation records (5247) of 1200 Murrah buffaloes spread over 37 years (1970 – 2006) were analyzed for evolving correction factors to adjust the data for non-genetic factors by time series analysis. The traits considered were age at first calving (AFC), lactation total milk yield (LTMY), lactation 305–day or less yield (L305DMY), lactation length (LL), calving interval (CI) and service period (SP). The overall least squares population means for these traits were 1349.39±6.33 days, 1841.90±32.62 kg, 1775.79±31.93 kg, 273.54±2.64 days, 428.30±3.54 days and 112.25±2.87 days, respectively. The seasonal and cyclical components of these traits were isolated. A periodicity of 7, 7, 7, 7, 6 and 6 years was observed in the above traits. The periodic function was fitted and it explained maximum variation in the above traits ranging from 34.18 (LTMY) to 99.01% (LL) revealing the periodicity of data over the years for majority of traits in Murrah buffaloes. Hence, the animal breeding data has to be adjusted for cyclicity over the years. Further, the monthly/seasonal indices estimated by ratio to trend method accounted for more environmental fluctuations and were more appropriate for decomposing the time series data than link relative method.